Mitochondrion-processed TERC regulates senescence without affecting telomerase activities - Qian Zheng; Peipei Liu; Ge Gao; Jiapei Yuan; Pengfeng Wang; Jinliang Huang; Leiming Xie; Xinping Lu; Fan Di; Tanjun Tong; Jun Chen; Zhi Lu; et al. (Protein & Cell, 2019)
Abstract Mitochondrial dysfunctions play major roles in ageing. How mitochondrial stresses invoke downstream responses and how specificity of the signaling is achieved, however, remains unclear. We have previously discovered that the RNA component of Telomerase TERC is imported into mitochondria, processed to a shorter form TERC-53, and then exported back to the cytosol. Cytosolic TERC-53 levels respond to mitochondrial functions, but have no direct effect on these functions, suggesting that cytosolic TERC-53 functions downstream of mitochondria as a signal of mitochondrial functions. Here, we show that cytosolic TERC-53 plays a regulatory role on cellular senescence and is involved in cognition decline in 10 months old mice, independent of its telomerase function. Manipulation of cytosolic TERC-53 levels affects cellular senescence and cognition decline in 10 months old mouse hippocampi without affecting telomerase activity, and most importantly, affects cellular senescence in terc −/− cells. These findings uncover a senescence-related regulatory pathway with a non-coding RNA as the signal in mammals.